The Australian 2019/2020 Black Summer Bushfires: Analysis of the Pathology, Treatment Strategies and Decision Making About Burnt Livestock - Cowled, Brendan D.; Bannister-Tyrrell, Melanie; Doyle, Mark; Clutterbuck, Henry; Cave, Jeff; Hillman, Alison; Plain, Karren; Pfeiffer, Caitlin; Laurence, Michael; Ward, Michael P. (Frontiers in Veterinary Science, 2022)
In 2019/2020, Australia experienced a severe bushfire event, with many tens of thousands of livestock killed or euthanised. Little systematic research has occurred to understand livestock bushfire injuries, risk factors for injury, or how to make decisions about management of bushfire-injured livestock. Addressing this research gap is important as there is an increasing bushfire incidence globally. This paper presents qualitative research findings about bushfire-injured and killed livestock in the south-east of Australia after the 2019/2020 Australian bushfires. The approach taken was to describe the pathology, treatments used, risk factors for injury and then to undertake thematic analysis to understand what affected decision making about how to manage injured livestock and any improvements. Livestock injured by the fires showed pathology predominantly associated with the common integument (feet, hooves and skin) and signs of acute respiratory damage. It could take several days for the full extent of burns to become apparent leaving prognostic doubt. Treatment strategies included immediate euthanasia, salvage slaughter, retention for later culling, treatment and recovery on farm, hospitalization and intensive treatment or no intervention. Risk factors reported for livestock injury included lack of warnings about an impending fire, the type and amount of vegetation around livestock and the weather conditions on the day the fire reached livestock. Moving stock to a protected area with little vegetation was seen as protective. Decision making about what to do with injured livestock and appeared influenced by three main themes: (1) observations on the severity of pathology, clinical signs and level of prognostic doubt, (2) pre-existing beliefs (animal welfare) and (3) assumptions about the future. The management of livestock was largely efficient and appropriate due to the rapid application of expert veterinary expertise. However, it is likely that some excess euthanasia of injured livestock occurred on veterinary advice with impacts on farmers. In future resourcing a response to enable regular re-visits of injured livestock to manage risks associated with gradual progression of burn pathology may reduce any excess euthanasia. In addition, a more comprehensive burns classification system linked to prognosis that can be rapidly applied in the field may assist assessments.